An efficient tool for metabolic pathway construction and gene integration for Aspergillus niger. (December 2017) - Sarkari, Parveen; Marx, Hans; Blumhoff, Marzena L.; Mattanovich, Diethard; Sauer, Michael; Steiger, Matthias G.
Graphical abstract: Highlights: GoldenMOCS allows easy metabolic pathway construction for multiple microorganisms. Heterologous pathway integration into a defined locus on the A. niger genome. Direct and defined CRISPR/Cas9 based genomic integration of circular plasmid DNA. The use of a pyrG split-marker reduces the screening work. Abstract: Metabolic engineering requires functional genetic tools for easy and quick generation of multiple pathway variants. A genetic engineering toolbox for A. niger is presented, which facilitates the generation of strains carrying heterologous expression cassettes at a defined genetic locus. The system is compatible with Golden Gate cloning, which facilitates the DNA construction process and provides high design flexibility. The integration process is mediated by a CRISPR/Cas9 strategy involving the cutting of both the genetic integration locus ( pyrG ) as well as the integrating plasmid. Only a transient expression of Cas9 is necessary and the carrying plasmid is readily lost using a size-reduced AMA1 variant. A high integration efficiency into the fungal genome of up to 100% can be achieved, thus reducing the screening process significantly. The feasibility of the approach was demonstrated by the integration of an expression cassette enabling the production of aconitic acid in A. niger .